Climate Change and Public Health in Europe: Impacts, Adaptation Measures, and Policy Implications (Academicia Review-A Multidisciplinary Online Journal, 2025)
Climate change is increasingly recognized as a major public health threat in Europe, affecting morbidity, mortality, and health system resilience. Rising temperatures, extreme weather events, air pollution, and changing disease patterns pose complex and interconnected risks to population health. This paper reviews recent scientific evidence (2024–2025) on the health impacts of climate change in Europe and evaluates adaptation strategies aimed at protecting public health. Using a structured literature review, key health outcomes, vulnerable populations, and policy responses are analyzed. A comparative reading table summarizes major findings across recent studies. The paper highlights gaps in preparedness, emphasizes health-equity-oriented adaptation, and discusses policy implications for strengthening climate-resilient health systems in Europe.
Keywords: Climate change; public health; Europe; health adaptation; limate resilience